Peramalan Pola Curah Hujan Di Kota Makassar Menggunakan Model Rantai Markov - Hisyam Ihsan; Wahidah Sanusi; Hasriani (Jurusan Matematika FMIPA UNM, 2019)
Markov chain is a method that studies the properties of a variable at the present time based on the nature of the properties in the past in an effort to estimate the properties of the same variable in the future. One of the methods commonly used in predicting the events that will be coming is the method of markov chain discrete. The purpose of this study is: (1) determine the order of the markov chain used in predicting the precipitation; (2) form the model of the markov chain each station in the predicted precipitation is in the City of Makassar; (3) know the results of the prediction of rainfall of each station using a markov chain. By using the method of markov chain discrete then it can be obtained the prediction results of the steady state Station Panaikang in the period of the 10th with a chance to 0.35 months experiencing dry conditions, of 0.11 months experience humid conditions and 0.55 months experience wet conditions. Station Biring Romang in the period of to-15 with a chance of 0.33 months experiencing dry conditions, of 0.08 months experience humid conditions and of 0.59 month is experiencing wet conditions. While on the station of Paotere in the period to 12 with opportunities to 0.39 months experiencing dry conditions, of 0.06 months experiencing the condition moist and 0.55 months experience wet conditions.